EFEKTIVITAS PENGGUNAAN MEDIA PEMBELAJARAN HURUF HIJAIYAH BERBASIS MULTIMEDIA TERHADAP KEMAMPUAN MEMBACA AL-QURAN PESERTA DIDIK KELAS III SD NEGERI 1 PAREPARE - Wahyuni Munir (IAIN PAREPARE, 2017)
This study discusses the Effectiveness of Using Hijaiyah Letters Learning Media Based Multimedia toward al-Quran reading Ability of the third grade students in SD Negeri 1 Parepare. The purpose of this thesis to know the al-Quran reading ability of students before and after Hijaiyah Letters Learning Media based Multimedia applied and then to know the the Effectiveness of Using Hijaiyah Letters Learning Media Based Multimedia toward al-Quran reading Ability of the third grade students in SD Negeri 1 Parepare.This type of research is a true-experimental research. The True-experimental research design used is Pre-Test and Post-Test Control Group Design, which means that there are two groups selected at random, then given pre test to know the initial state is there any difference between the experimental group and the control group. Data source is all students of the third grade students in SD Negeri 1 Parepare that is class III a and III b; Research instruments are Observation Sheet, reading test of Quran and Student Response Questionnaire; Data collection techniques are Observation, Test, and Questionnaire Technique; Processing Technique and analysis data includes Descriptive Statistics and Infrensial Statistics Analysis which includes Normality Test, Homogeneity Test, and Hypothesis Testing. The results of this research are: (1) The students of the experimental class and the control class have the ability to read al-Quran before being given treatment using Hijaiyah Letters Learning Media Based Multimedia. Both fall into the category quite smoothly. Then, al-Quran reading ability of experimental class after being treated better than the results of post-test control class, where the average result of the experimental class is 74.78 while the control class is 63.19 and belong to the category quite smoothly (2) The use of Hijaiyah Letters Learning Media Based Multimedia, proved to be effective can improve students' reading ability of the Quran. This result is proved by the increase of al-Quran reading ability, students activity during learning is good and student's response to learning activity is positive.